Self-assembly of modified rhodamine-6G with tri-block copolymer: unusual vesicles formation, pH sensing and dye release properties - Praveen, L.; Saha, Sukdeb; Jewrajka, Suresh K.; Das, Amitava (Journal of Materials Chemistry B, 2013)
A new rhodamine-6G derivative having a C18-alkyl chain self-assembles with an amphiphilic tri-block copolymer and forms stable vesicles in water or in water–ethanol (4 : 1, v/v) medium. The stability of the spirolactam form of the rhodamine-6G derivative in these vesicular structures, along with studies of controlled dye release and pH sensing are discussed. Transmission electron micrographs and DLS analyses confirm the formation of vesicular structures. Atomic force microscopy (AFM) images show that the self assembled tri-block copolymer-octadecyl rhodamine vesicles form near spherical nanostructures with a size ranging from 80 to 110 nm. Furthermore, the vesicular system is disassembled under acidic conditions, releasing the cargo which are an integral part of the vesicle. Dye-release studies showed that the release rates of the loaded dye in the vesicles could be well-controlled as a function of the media pH. These results offer an opportunity to use these nanovesicles as imaging reagents for probing media pH with their simultaneous use as nanocarriers for intracellular drug delivery.